2016
DOI: 10.1002/pi.5102
|View full text |Cite
|
Sign up to set email alerts
|

Poly(lactic acid)‐based nanocomposites filled with cellulose nanocrystals with modified surface: all‐atom molecular dynamics simulations

Abstract: Polymer bio-nanocomposites are widely used nowadays in various applications. One of the most promising polymers for producing such materials is poly(lactic acid) (PLA) filled with cellulose nanocrystals (CNCs). To increase the compatibility of hydrophobic PLA and hydrophilic cellulose, the surface of the latter can be chemically modified. Among the various surface modifications, the grafting of lactic acid oligomers (OLAs) is of special interest. In this paper, the first all-atom molecular dynamics simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 64 publications
3
41
0
Order By: Relevance
“…Following our previous simulations [18][19][20][21], we performed atomistic molecular dynamics simulations of polylactide-based nanocomposites filled with surface-modified cellulose nanocrystals (CNC). The simulated systems comprised 20 free lactide chains that surrounded the filler, with the length of the free chains equal to 150.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following our previous simulations [18][19][20][21], we performed atomistic molecular dynamics simulations of polylactide-based nanocomposites filled with surface-modified cellulose nanocrystals (CNC). The simulated systems comprised 20 free lactide chains that surrounded the filler, with the length of the free chains equal to 150.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…In our previous studies, the unusual behavior of the grafted lactide chains was observed by using atomistic molecular dynamics (MD) simulation when attempting to reproduce the known influence of the grafting density on the grafted layer structures [18,19]. Despite their dipolar nature, the lactide chains, being aliphatic ester chains, may initially seem to be the conventional grafts that were considered earlier [10][11][12][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations